Note on taxonomy and typification of Vigna hainiana Babu, Gopinathan & Sharma ( =Phaseolus wightii W. & A.) - Nayar, E. Roshini (Rheedea, 1994)
Vigna hainiana Babu, Gopinathan & Sharma, collected from north-western and eastern parts of India, has been studied. Characters for differentiating this species have been delineated. The type indicated previously for V. hainiana was incorrect; Wall. L. n. 5591 is the lectotype for this species.